Proses Berpikir Numerik dalam Menyelesaikan Soal Cerita Materi FPB dan KPK Kelas IV SD Berbasis Kearifan Lokal - Lolitha Arum Permatasari; Feny Rita Fiantika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to analyze students' numerical thinking processes in solving FPB and KPK story problems based on local wisdom, as well as to identify effective learning strategies to improve students' numerical abilities. The research method used is a qualitative method with a descriptive approach. Data collection was carried out through numerical thinking process tests, interviews with students and teachers, and observation of learning implementation. The research subjects consisted of 29 class IV students at SDN Wonokromo III Surabaya who were grouped based on high, medium and low abilities. Data was analyzed through reduction, presentation and verification. The research results show that students with high ability (MY) can solve questions well, showing strong and consistent numerical abilities. Students with moderate abilities (RP) are able to solve several questions, but still need improvement in understanding the KPK concept. Low ability (MM) students experienced difficulty in all questions, indicating the need for deeper and more focused learning strategies. The integration of local context in mathematics learning has proven effective in increasing student engagement and understanding.